Nursing assistance for the family of premature newborns in the Intensive Care Unit (Research, Society and Development, 2022)
Objectives: To analyze the nursing care provided to the family of premature newborns in the Intensive Care Unit. Method: Integrative literature review in which primary data were used in the LILACS, MEDLINE and BDENF databases with established criteria for searching for journals in Portuguese, English and Spanish through the research modalities and levels of evidence in the period of 5 years (2010-2021). Results: Information about the 10 articles contained in the discussion of this literature review is presented. All the results were interpreted and synthesized, through a comparison of the data evidenced in the analysis of the articles. Discussions: It is noticed in some studies that the birth of a premature baby brings to the family an intense confrontation between the imaginary NB and the real NB. The representations about the NB built during pregnancy are gradually deconstructed and slowly their image as a newcomer is assimilated. Conclusion: The study reveals that families who experience this moment of prematurity in the NICU have reactions and feelings that make it difficult to cope with this situation. Despite several negative feelings, characterized as powerless and frightened, family members show positive expectations, since they believe in the treatment and recovery of the NB's health.